2015
DOI: 10.1002/2015gl063693
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of organic aerosol: The gap between ambient and laboratory measurements

Abstract: A large data set including surface, aircraft, and laboratory observations of the atomic oxygen‐to‐carbon (O:C) and hydrogen‐to‐carbon (H:C) ratios of organic aerosol (OA) is synthesized and corrected using a recently reported method. The whole data set indicates a wide range of OA oxidation and a trajectory in the Van Krevelen diagram, characterized by a slope of −0.6, with variation across campaigns. We show that laboratory OA including both source and aged types explains some of the key differences in OA obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
83
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 66 publications
20
83
2
Order By: Relevance
“…Aerosol elemental ratios measured with the AMS have been previously used to distinguish between different types of organic aerosol Ng et al, 2010), examine the degree to which chamber SOA is able to simulate ambient SOA (Chhabra et al, 2010;Ng et al, 2010), and to constrain oxidation mechanisms used in theoretical models Kroll et al, 2011;Donahue et al, 2011;Daumit et al, 2013;Chen et al, 2014). Here we show that while the changes introduced by the Improved-Ambient method can be significant, they do not change any fundamental conclusions made from previous AMS studies.…”
Section: Atmospheric Implicationsmentioning
confidence: 50%
See 1 more Smart Citation
“…Aerosol elemental ratios measured with the AMS have been previously used to distinguish between different types of organic aerosol Ng et al, 2010), examine the degree to which chamber SOA is able to simulate ambient SOA (Chhabra et al, 2010;Ng et al, 2010), and to constrain oxidation mechanisms used in theoretical models Kroll et al, 2011;Donahue et al, 2011;Daumit et al, 2013;Chen et al, 2014). Here we show that while the changes introduced by the Improved-Ambient method can be significant, they do not change any fundamental conclusions made from previous AMS studies.…”
Section: Atmospheric Implicationsmentioning
confidence: 50%
“…The Improved-Ambient method yields van Krevelen slopes that are approximately 20 % shallower than those determined with the Ambient-Aiken method. Details are discussed in Chen et al, 2014. These slopes (−0.8 for total OA and −0.4 for OOA) suggest that the ambient OA oxidative mechanisms involve different net addition of -OH and/or -OOH functionalities and fragmentation than previously assumed.…”
Section: Effect Of Improved-ambient Methods On Previous Measurements Omentioning
confidence: 78%
“…The O : C vs. H : C ratios can be fitted by a line with a slope of −0.63 and an intercept of 1.95 by the reduced-major-axis (RMA) regression method. The V-K diagram for OA summarized by Chen et al (2015) is also given in Fig. 9 in order to make comparisons between OA measured in Beijing and in other atmospheric environments.…”
Section: Closure Between Particle Hygroscopicity and Chemical Componentsmentioning
confidence: 99%
“…9 in order to make comparisons between OA measured in Beijing and in other atmospheric environments. Chen et al (2015) found that ambient organic aerosols line up in the V-K space along a line with a slope of −0.6 by synthesizing a large data set of surface field observations covering urban, rural, and remote environments. The trajectory Atmos.…”
Section: Closure Between Particle Hygroscopicity and Chemical Componentsmentioning
confidence: 99%
“…Modeling has shown that including cloud processing reactions improves prediction of secondary organic aerosol (SOA) mass concentrations . However, there is substantial inconsistency between the chemical composition of laboratory-generated and ambient organic aerosol, in part likely due to aqueous processing (Chen et al, 2015). Potential products of aqueous processing include carboxylic acids, esters, organosulfur compounds, polyols, amines, amino acids, and highly oxygenated oligomeric species (Blando and Turpin, 2000;Ervens et al, 2011).…”
mentioning
confidence: 99%